Prinjatie resenija kak faktor effektivnosti igrovoj dejatel'nosti - Nepopalov, V. N.; Abalyan, A. G. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
As a result of the experimental research carried out by the authors there have been received the data on the factors determining the speed and the contents of decision-making. The subjective conditions of the decision-making that determine a situational choice, have been revealed.